Bond strength of locator housing attached to denture base resin secured with different retaining materials - Mohammadreza Nakhaei; Hossin Dashti; Atefe Baghbani; Zahra Ahmadi (Wolters Kluwer Medknow Publications, 2020)
Background: The type of housing retaining material may affect the bond strength of the housing to denture base resin. The aim of this in vitro study was to evaluate the bond strength of locator housing attached to polymethyl methacrylate (PMMA) denture base resin secured with different retaining materials. Materials and Methods: In this in vitro study Forty-four PMMA blocks (10 mm × 15 mm × 15 mm) were prepared with a central cylindrical canal inside to allow the insertion of locator housings. The prepared specimens were then randomly divided into four groups (n = 11). Each group received one of the following retaining materials for housing insertion: Auto-polymerized acrylic resin (APAR), auto-polymerized composite resin (Quick up), application of alloy primer on titanium housing plus Quick up (AL-Quick), and heat-polymerized acrylic resin (HPAR). The specimens were thermocycled 5000 times between 5°C and 55°C, followed by 1000 cycles of vertical insertion separation on the locator abutment. A push-out force was applied on the flat back surface of the housing after which the failure and shear bond strength values were calculated. The data were analyzed using one way-ANOVA and Games-Howell test (α = 0.05). Results: HPAR group had significantly higher shear bond strength values compared to the other groups (P < 0.05). No significant differences were found among the other remaining material groups (P > 0.05). Conclusion: Inserting of locator housing using HPAR resulted in higher bond strength between housing and denture base resin. The application of alloy primer did not improve the bond strength of locator housing which was retained with "Quick up".